A influência da Pandemia da Covid-19 no Investimento Social Privado (ISP) do setor de energia: estudos de caso de empresas listadas no ISE-B3 e seus institutos - Silva, Vagner Antonio da (2022)
The Covid-19 Pandemic surged on China at the end of 2019 implied in radical changes and new approaches for the humankind on how to deal individually with itself, with the other and the collective of people. Many people quickly have lost their lives, forcing the adoption of dramatic measures leading to the social distancing to avoid the disease dissemination, the health decrease of people and more deaths. These measures led the society to experience a health and economic crisis. Those among the population most socioeconomically vulnerable had to count on the support of others’ donations looking to safely pass, yet at the beginning of 2020, an unknown tenure related to how long in time the pandemic would still pressing their day to day lives. Big corporations with stocks options on the market in the local B3 stock exchanges, engaged in donation actions docked to their sustainability processes and systems, participating on the local corporate sustainability index, called ISE – “Índice de Sustentabilidade Empresarial”. To the understanding of how the covid-19 pandemic have influenced in the decision process of these corporations doing part of the ISE-B3 related to the lenses of the corporate sustainability (CS), corporate social responsibility (CSR), and projects based on private grants and the relationship with the stakeholders, the current applied research is based in the consultation of their annual sustainability reports, as well as the foundations or institutes financially supported by this corporations, regarded to the year of 2020, further the contributions of specialists on the theme. As comparison parameter the 2017 to 2019 annual sustainability reports of the same companies also were consulted and compiled. The intention is comprehend: “how the covid-19 pandemic influenced the ISE-B3 companies’ private grants/CSR agenda?”. Were identified changes on the way companies considered their strategies to communicate the highlights on the initiatives implemented during the chosen period. Conclusions that come up under the covid-19 pandemic and stakeholders influence on the business demonstrated the quick response not only to the external social demands but, also and effectively, to that public most intimate and responsible for the continuity of the business operations at a level that allow these companies aid that most vulnerable public with effectiveness: the coworkers and the suppliers. The response also positively signals to the market due to the raising concern on the ESG management, which in Brazil is called ASG, and bring some patterns using the content, data and disclaimers integrating the annual corporate sustainability reports.